2014
DOI: 10.3892/or.2014.3073
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 activates p53 and elevates p21 gene expression in cancer cells and the mouse colon

Abstract: Abstract. Increasing evidence indicates vitamin B 6 acts as a protective factor against colon cancer. However, the mechanisms of the effect of vitamin B 6 are poorly understood. The present preliminary study using DNA microarray and realtime PCR indicates p21 mRNA is upregulated in human colon carcinoma (HT29) cells exposed to pyridoxal (PL, 500 µM). A similar effect was observed in human epithelial colorectal adenocarcinoma (Caco2) cells, human colon adenocarcinoma (LoVo) cells, human embryonic kidney (HEK293… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This is consistent with a report indicating that PDXK expression was positively correlated with overall survival of NSCLC patients treated with cisplatin. Treatment of human colon cancer and HEPG2 cells with 0.5-mM PL increased the expression of the cyclin inhibitor p21 as the result of p53 repression [90]. Similarly, PL treatment of HT29 colon cancer and HEPG2 cells increased the expression of insulin growth factor binding protein 1, a tumor suppressor [84]; the same finding was reported in MCF-7 breast cancer cells [84].…”
Section: Pyridoxine B6supporting
confidence: 61%
“…This is consistent with a report indicating that PDXK expression was positively correlated with overall survival of NSCLC patients treated with cisplatin. Treatment of human colon cancer and HEPG2 cells with 0.5-mM PL increased the expression of the cyclin inhibitor p21 as the result of p53 repression [90]. Similarly, PL treatment of HT29 colon cancer and HEPG2 cells increased the expression of insulin growth factor binding protein 1, a tumor suppressor [84]; the same finding was reported in MCF-7 breast cancer cells [84].…”
Section: Pyridoxine B6supporting
confidence: 61%
“…Less is known about potential regulatory roles of other vitamins, including those that function as true enzyme cofactors in the metabolic network. However, gene expression profiling in mammalian cells has revealed transcript-level responses to vitamins B1 (thiamine) ( Fraser et al, 2012 ; Liu et al, 2004 ) ( Tanaka et al, 2007 ), B2 (riboflavin) ( Nakano et al, 2011 ), B3 (nicotinamide/niacin) ( Choi et al, 2011 ; Couturier et al, 2014 ; Giammona et al, 2006 ), B6 (pyridoxal 5′ phosphate, PLP) ( Toya et al, 2012 ; Zhang et al, 2014 ), B9 (folic acid) ( Barua et al, 2014 ; Champier et al, 2012 ; Lin et al, 2011 ), C (ascorbic acid) ( Canali et al, 2014 ; Jun et al, 2011 ; Takahashi et al, 2014 ), and E (tocopherol/tocotrienols) ( Landrier et al, 2010 ; Makpol et al, 2013 ; Mustacich et al, 2009 ). The mechanisms behind, and consequences of, these observed vitamin-induced gene expression changes have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, a recent study suggested that vitamin B 6 species could inhibit the activation of NF-κB, which is involved in the inflammatory response, and nucleotide-binding oligomerisation domain, Leucine-rich Repeat and Pyrin domain containing-mediated caspase-1 activation, which suppresses cytokine production (44) . Postulated anti-inflammatory mechanisms relevant for CRC patients include activation of p53 and p21 tumour suppressor gene expression in the colon (45,46) . Moreover, human colon carcinoma cell line studies demonstrated that vitamin B 6 induced a reduction in inflammatory cytokine (including IL-6 and TNFα) secretion from peripheral blood mononuclear cells (47) .…”
Section: Discussionmentioning
confidence: 99%